Multilevel Security System Using Raspberry Pi3 - M, Karthikeyan; KA, Gowrishankar.; Sekar. G, Rajith; Elamaran, E; Sudhakar, B (International Journal of Engineering and Technology, 2018)
In this modern world security has become a major concern in securing a particular area such as banks, institution, temple premises etc. The existing system can be easily broken either by hacking the password or by duplicating entry cards. There are some security system which are very difficult to break but they are neither cost efficient nor easily affordable. We proposed a strong secure and affordable system using RFID, PIN lock and face recognition using raspberry pi3.